1985
DOI: 10.1007/bf00339559
|View full text |Cite
|
Sign up to set email alerts
|

The histotoxicity of cyanoacrylates

Abstract: Cyanoacrylates, a group of rapidly polymerizing adhesives, have found widespread uses in oral and general surgery as well as surgical subspecialties, for example as hemostatic and anastomotic agents. They have been utilized most recently as materials for embolotherapy of complex cerebral and extra-cerebral vascular anomalies. The histopathology that results from their deposition in human tissues is thus an important consideration, and the subject of this review. Particular attention is given to the fate of cya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
93
0
2

Year Published

1990
1990
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(98 citation statements)
references
References 105 publications
1
93
0
2
Order By: Relevance
“…However, shorter chain derivatives such as ethyl cyanoacrylate have been found to be more histotoxic than longer chain derivatives 21,22 . This method is simpler and more time efficient due to the use of curved irrigation cannulae with olive tips.…”
mentioning
confidence: 99%
“…However, shorter chain derivatives such as ethyl cyanoacrylate have been found to be more histotoxic than longer chain derivatives 21,22 . This method is simpler and more time efficient due to the use of curved irrigation cannulae with olive tips.…”
mentioning
confidence: 99%
“…Bacterial genome experiments have demonstrated that NBCA and IBCA are mutagenic; however, they have not been proven to be carcinogenic [6]. NBCA is applied to skin wounds to achieve hemostasis.…”
Section: Cyanoacrylatesmentioning
confidence: 99%
“…Possible complications of cyanoacrylate varicocele embolization are glue migration into the pulmonary circulation, a glued catheter and severe phlebitis of the gonadal vein or pampiniform plexus (26)(27)(28). We had no complications in our series because the glue embolization was performed by radiologists with considerable experience in the use of tissue adhesives.…”
Section: Discussionmentioning
confidence: 89%